First case reports of intentional Imepitoin overdose in humans: A case of two patients - Gerard Ronda-Roca; Antonio F. Caballero-Bermejo; José Cantillana-Barrenas; Belén Ruiz-Antorán (Toxicology Reports, 2025)
We report two cases of acute imepitoin overdose, a partial GABA-A receptor agonist. The first case involved a caucasian women of 22-year-old patient who ingested 20-24 g of imepitoin in a suicide attempt, presenting with central nervous system depression and mydriasis. The second case involved a caucasian male of 31-year-old patient who ingested 6–8 g of imepitoin along with other psychiatric medication, paracetamol, and ibuprofen. This patient presented with somnolence and bradylalia. Both patients received supportive care, including airway protection, intravenous fluids, activated charcoal, and cardiac monitoring. In the second case, flumazenil was administered and later discontinued. Both patients recovered fully within hours without complications. Imepitoin acts at the benzodiazepine binding site of the GABA-A receptor, approved for canine epilepsy and scarcely studied in humans, producing anxiolytic and anticonvulsant effects with reduced risk of sedation, dependence, or tolerance. It has a rapid absorption profile (Tmax 0.5–2 h) and a variable half-life, shorter in smokers due to CYP1A2 induction.